Fungal Resilience and Shifting Phenology in the Face of Climate Change (International Journal of Food and Nutritional Sciences, 2023)
Climate change significantly affects ecosystems and biodiversity, especially impacting fungal communities and their life cycles. As temperatures rise and rainfall patterns change, fungi—particularly mushrooms—experience shifts in their growth and reproductive patterns, which can alter their ecological roles. This review explores how climate change influences fungal life cycles and discusses its effects on ecosystems, agriculture, and human health. We examine how changes in when and how often mushrooms fruit, as well as shifts in where fungi are found, disrupt important relationships with plants and affect decomposition processes that are vital for nutrient cycling. The review also looks at how rising temperatures can lead to more fungal diseases, posing risks to food security and human health. Lastly, we highlight conservation strategies that focus on protecting fungal diversity and restoring ecosystems to help them adapt to climate change. Understanding these impacts will help us better manage fungi and their essential roles in nature.